2021
DOI: 10.1111/rda.13887
|View full text |Cite
|
Sign up to set email alerts
|

Morphological reproductive characteristics of testes and fertilization capacity of cryopreserved sperm after the Fukushima accident in raccoon (Procyon lotor)

Abstract: Since the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, we have established an archive system of livestock and wild animals from the surrounding ex‐evacuation zone. Wildlife within the alert zone have been exposed to low‐dose‐rate (LDR) radiation for a long continuous time. In this study, we analysed the morphological characteristics of the testes and in vitro fertilization (IVF) capacity of cryopreserved sperm of racoons from the ex‐evacuation zone of the FDNPP accident. The radioactivity of caesium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(42 reference statements)
2
4
0
Order By: Relevance
“…Data obtained in this work are in agreement with previous studies demonstrating no significant differences in the male reproductive system of wild animals exposed to LDR radiation after the Fukushima accident [19,26,27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Data obtained in this work are in agreement with previous studies demonstrating no significant differences in the male reproductive system of wild animals exposed to LDR radiation after the Fukushima accident [19,26,27].…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, Takino and colleagues [19] (2017) investigated the effect of chronic LDR radiation on spermatogenic cells in A. speciosus, finding enhanced spermatogenesis. In contrast, significant changes were not observed in raccoon testes after long-term exposure to ionizing radiation [26], or in the in vitro fertilizing capacity of cryopreserved sperm of A. speciosus after chronic LDR radiation exposure [27].…”
Section: Introductionmentioning
confidence: 81%
“…Legendre et al (2016) also identified that low‐dose depleted uranium could affect the production of these sex steroid hormone levels in adult rats. Interestingly, we did not detect acute physiological damages/changes in the male reproductive organ, including testis and epididymis, consistent with the latest finding that chronic LDR exposure associated with the Fukushima plant accident did not affect the characteristics and functions of male raccoons' reproductive system (Ashoub et al, 2021; Komatsu et al, 2020). Nevertheless, the current study found that LDR indeed increased the content of testosterone without the remarkable detectable damages in radiosensitive organs.…”
Section: Discussionsupporting
confidence: 90%
“…In another study focusing on raccoon testes, although the total amount of radiation was unknown, chronic LDR exposure associated with the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident had no adverse effect on their reproductive characteristics and functions. [ 50 ]. Moreover, enhanced spermatogenesis occurred in large Japanese field mice ( Apodemus speciosus ) living in and around the FDNPP ex-evacuation zone (407–447 μGy/day) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%